Factors Influencing Students’ Resistance To Change And Intention To Use Mobile Learning In Saudi Arabia - Jassim H, Alsihati Essa (2023)
This study examined the effect of UTAUT (Performance Expectancy, Effort Expectancy, Lecturer Influence & Facilitating Condition) and MIR (Attitude, Personal Innovativeness, Self-efficacy, Self-Management of Learning & Inertia) on the m-learning resistance and intention to use m-learning among the universities students in Higher Education in Saudi Arabia under the premises of UTAUT and MIR models. Quantitative data was collected from randomly selected 358 students based on the five best-ranked and well reputed educational institutions in Saudi Arabia. Findings of the study revealed that performance expectancy, effort expectancy, lecturer influence, facilitating conditions, self-efficacy and self-management of learning positively significant impact of intention to use m-learning, meanwhile, performance expectancy, lecturer influence, facilitating conditions, personal innovativeness and self-efficacy positively significant impact of m-learning resistance.